Pengaruh Pengetahuan Investasi, Ekspektasi Return dan Pemahaman Kemajuan teknologi Terhadap Minat Investasi Mahasiswa di Pasar Modal - Andi Iqbal Hidayat, Andi; Suhaedi, Wirawan (Fakultas Ekonomi dan Bisnis Unram, 2024)
The focus of this research is to analyze and test the significance of the influence of investment knowledge, return expectations and partial understanding of technological progress on FEB Unram students' investment interest in the capital market. The respondents of this research were all FEB Unram students who had invested in the capital market, who were gathered in KSPM UKM totaling 65 people. The analysis tool uses PLS analysis. The PLS analysis work process with algorithm settings and bootstrapping found that the resulting model, both the outer model and inner model, was suitable for use to prove the hypothesis (R square value 0.520 and chi square greater than 0.00). Referring to the positive original sample value and the calculated t value which is greater than the t table for each association between variables, it can be stated that there is a positive and significant influence of investment knowledge, return expectations and understanding of technological progress on investment interest of FEB Unram students in capital market. Students who are interested in investing to get returns and making it a profession absolutely must increase their knowledge and skills in the field of investment, the ability to calculate returns and the ability to run applications related to investing in the capital market.